PENGARUH PERSEPSI INFORMASI DAN HIBURAN TERHADAP NIAT PEMBELIAN KONSUMEN DENGAN KEPERCAYAAN PADA SITUS WEB SEBAGAI MEDIASI (STUDI PADA KONSUMEN LAZADA.CO.ID DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA BANDA ACEH) - Kharisma Alam, Muhammad Adam (Departemen Manajemen, 2017)
This study aims to determine the effect of perceived informativeness and entertaiment on consumer purchase intentions with variables trust as mediators. The sample used in this study is 100 respondents who are customers of Lazada.co.id Banda Aceh. Purposive Sampling is used as a sampling technique. Partial Least Square analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that perceived informativeness and entertaiment has effect on purchase intention. In addition, the results obtained that the trust variables partially influence the perceived informativeness to purchase intentions, and variables full mediatingl influence the perceived entertaiment to purchase intentions. The higher perceived informativeness and entertaiment, the higher the trust, the stronger the purchasing intention of the consumer.